Culture of Arterial Endothelial Cells - Booyse, Francois M; Sedlak, Bonnie J; Rafelson, Max E, Jr. (Thrombosis and Haemostasis, 1975)
Arterial endothelial cells were obtained from bovine aortae by mild treatment with collagenase and medium perfusion. These cells were cultured in RPMI-1640 medium containing 15 mM Hepes buffer and 35% fetal calf serum at pH 7.35. Essentially ah (90–95%) the effluent cells were viable and 80% of these cells attached to the substratum within 1 hour. Small patches of attached cells coalesced to form confluent monolayers in 3–5 days. Confluent monolayers of endothelial cells consisted of a homogeneous population of tightly packed, polygonal cells. Selected cultures were serially subcultured (trypsin-EDTA) for 12–14 months (30–35 passages) without any apparent change in morphology or loss of growth characteristics. Primary and three-month old (15 passages) cultures had population doubling times of 32–34 hours and 29–31 hours, respectively. These cells (primary and subcultures) did not require a minimum cell number to become established in culture. Bovine endothelial cells (primary, first, fifth and thirteenth passages) were characterized ultrastructurally by the presence of Weibel-Palade bodies, pinocytotic vesicles and microfilaments and immunologically by the presence of thrombosthenin-like contractile proteins and Factor VIII antigen. The intercellular junctions of post-confluent cultures stained specifically with silver nitrate. From these data, we concluded that identifiable endothelial cells could be obtained from bovine aortae and cultured and maintained for prolonged periods of time.